Puisi Indonesia Abad ke-5: Kajian Struktural dan Sosiologi Sastra Teks Yūpa Muarakaman - Indra Sarathan; Widyo Nugrahanto; Randy Ridwansyah (Balai Bahasa Kalimantan Tengah, 2019)
The history of modern Indonesian poetry often begins in the 1920s. The first modern Indonesian poem refers to the poem ―Tanah Air‖ ‗Motherland‘ by Muhammad Yamin. The canonization of M. Yamin (1903—1962) as one of pillar modern Indonesian poetry was known from the contribution of A. Teeuw (1921—2012). The results of his research on Indonesian poetry continue to resonate in the spaces of literary and language education to this day (2018). However, there is still little attentions that explain the process of transformation from old poetry (mantra, pantun, karmina, seloka, gurindam, syair, etc.) to modern Indonesian poetry. The data only explained the milestones of modern Indonesian poetry starting in the 1920s. Even though the history of world literature dived until the time Before Century in his explanation of the history of poetry. Such as the Gilgamesh epic written on the 3rd century BC stone remains of the Sumerians in Mesopatami or the Beowulf long poem derived from oral literature as the beginning of the history of Anglo-Saxon (ancient English) poetry of the 8th century CE. Referring to the not strict definition of poetry, this paper will review the oldest text of the inscription in the Indonesia archipelago (5th century AD) as a form of old poetry by examining the structure and typology, as well as the social history of Indonesian ancient people that produced the inscription text in viewpoints sociology of literature. Thus, the results of this study are also expected to offer an alternative historiography of the history of Indonesian poetry.